Differences in weed seed banks in planted tree fallows in southwestern Nigeria - Kamara, A.Y.; Chikoye, David; Jutzi, S.C. (1999)
The weed seed bank under seven fallow tree species was analysed in size and composition five years after tree establishment. The seed bank was lower in Enterolobium cyclocarpum fallows than in the other tree fallows at both 0-5 and 5-10 cm depths. Nuclea latifolia and Terminalia superba tree fallows had the highest seed banks despite the fact that they had the highest floor litter cover. There was no correlation between light transmission and seed bank suggesting that other factors than shade were responsible for the differences in the seed bank observed in the different tree plantations. Generally, Talinum triangulare, sedges, Ageratum conyzoides, Spermacoce ocymoides, and Oldenlandia corymbosa were the dominant species in all tree fallows.